Analisis Kemampuan Menulis Teks Persuasif melalui Media Poster Lingkungan pada Siswa Madrasah Ibtidaiyah - Daniar Khumairotul Anwariyah; Kholik Kholik (Lingua Franca, 2026)
This research aims to conduct an in-depth analysis of fourth-grade students' persuasive writing skills through environmental posters at MI Ihyaussalafiyah. The primary focus is to investigate how students transform direct field observations into systematic and coherent text structures. This encompasses the ability to identify environmental issues, construct logical arguments, and employ effective persuasive vocabulary to influence readers. The study employs a qualitative case study method involving 16 fourth-grade students as subjects. Data were collected using the "observation and note-taking" (simak dan catat) technique to capture detailed writing processes. The data were then analyzed interactively using "identity and distributional" (padan dan agih) methods to comprehensively evaluate the situational context and linguistic structures produced by the students. The results indicate that field observations serve as highly effective empirical stimuli in triggering students' creative writing ideas. Students were able to transform environmental realities—such as leaking faucets and waste accumulation in the school area—into rational arguments and compelling calls to action. Writing assessment scores ranged from 76 to 92, placing students in the "Excellent" category, particularly in their ability to integrate textual messages with visual illustrations on posters. In conclusion, the use of environmental poster media has been proven to enhance persuasive writing skills and support the application of deep learning principles, including mindful, meaningful, and joyful learning. This media is highly effective as a pedagogical tool for developing systematic, critical, and contextual writing skills for elementary-level students.